Achieving a Complete Clinical Response After Neoadjuvant Chemoradiation That Does Not Require Surgical Resection: It May Take Longer Than You Think!. Issue 7 (July 2019) - Habr-Gama, Angelita; São Julião, Guilherme P.; Fernandez, Laura M.; Vailati, Bruna B.; Andrade, Andres; Araújo, Sérgio E. A.; Gama-Rodrigues, Joaquim; Perez, Rodrigo O.
Abstract : BACKGROUND: Patients with rectal cancer who achieve complete clinical response after neoadjuvant chemoradiation have been managed by organ-preserving strategies and acceptable long-term outcomes. Controversy still exists regarding optimal timing for the assessment of tumor response after neoadjuvant chemoradiation. OBJECTIVE: The purpose of this study was to estimate the time interval for achieving complete clinical response using strict endoscopic and clinical criteria after a single neoadjuvant chemoradiation regimen. DESIGN: This was a retrospective review of consecutive patients managed by 54-Gy and consolidation 5-fluorouracil–based chemotherapy. Assessment of response was performed at 10 weeks after radiation. Patients with suspected complete clinical response were offered watch-and-wait strategy and reassessment every 6 to 8 weeks until achievement of strict criteria of complete clinical response or overt residual cancer. SETTINGS: This study was conducted at a single tertiary care center. PATIENTS: Patients with complete clinical response who underwent a successful watch-and-wait strategy until last follow-up were eligible. Dates of radiation completion and achievement of strict endoscopic and clinical criteria (mucosal whitening, teleangiectasia, and no ulceration or irregularity) were recorded. Patients with incomplete response or with initial complete clinical response followed by local recurrence or regrowth were excluded. MAIN OUTCOMES MEASURES: The distribution of time intervals between completion of radiation and achievement of strict complete clinical response was measured. Patients who achieved early complete clinical response (⩽16 wk) were compared with late complete clinical response (>16 wk). RESULTS: A total of 49 patients achieved complete clinical response and were successfully managed nonoperatively. A median interval of 18.7 weeks was observed for achieving strict complete clinical response. Only 38% of patients achieved complete clinical response between 10 and 16 weeks from radiation completion. Patients with earlier cT status (cT2/T3a) achieved a complete clinical response significantly earlier when compared with those patients with more advanced disease (T3b-d/4; 19 vs 26 wk; p = 0.03). LIMITATIONS: This was a retrospective study with a small sample size. CONCLUSIONS: Assessment at 10 to 16 weeks may detect a minority of patients who achieve complete clinical response without additional recurrence after neoadjuvant chemoradiation. Patients suspected for a complete clinical response should be considered for reassessment beyond 16 weeks before definitive management when considered for a watch and wait strategy. See Video Abstract at http://links.lww.com/DCR/A901 .